Farming practices among hill paddy smallholders in Sg. Asap, Belaga, Sarawak - Allan, Rhemaneeta; Rosli, Anita; Daud, Adrian; Lepun, Philip; Alan, Ribka; Robin, Tunung; Saupi, Noorasmah; Aziz, Zakry Fitri Abdul; Hung, Patricia King Jie; Ramaiya, Shiamala Devi; Hassan, Suziana; Ismail, Zahora; et al. (Macrothink Institute, 2023)
Hill paddy cultivation is popular among the native people living in the eastern part of Malaysia, The Island of Borneo. A preliminary study focused on the background and farming practice of the hill paddy among smallholders in Sg. Asap, Belaga Sarawak (East Malaysia) is an initiative to enhance hill paddy cultivation and pursue self-sufficiency in overall rice production. A total of 30 respondent samples were collected from February to March 2023, and the samples collected were interpreted using descriptive analysis. The findings show that Kerawing, Alek, and Pulut were the most popular hill paddy varieties. Approximately 86.7 percent of the farmers cultivated hill paddy at least more than a hectare. The most common agricultural inputs used were herbicides and the least used fungicide. 73.4 percent of farmers harvested at least 1 tonne of hill paddy per hectare. Only 53.3 percent of the farmers chose to commercialise their yield. Besides, the study shows that the younger generation’s involvement is depleting, with zero study participants below 35. Sixty percent of the farmers claimed that generational practices are the reason behind their interest in hill paddy cultivation. With commercialisation and self-sufficiency as the target of the governing party, hill paddy cultivation has to be upscale and improved in terms of farm area, management practices, involvement training, and participation of the younger generation.